Oligodendrogenesis and myelinogenesis during postnatal development effect of glatiramer acetate. Issue 4 (30th January 2014) - From, Renana; Eilam, Raya; Bar‐Lev, Dekel D.; Levin‐Zaidman, Smadar; Tsoory, Michael; LoPresti, Patrizia; Sela, Michael; Arnon, Ruth; Aharoni, Rina
<x xml:space="preserve">Abstract</x> Myelinogenesis in the mammal nervous system occurs predominantly postnatally. Glatiramer acetate (GA), a drug for the treatment for multiple sclerosis (MS), has been shown to induce immunomodulation and neuroprotection in the inflamed CNS in MS and in experimental autoimmune encephalomyelitis (EAE). Here we investigated whether GA can affect myelinogenesis and oligodendrogenesis in the developing nervous system under nonpathological conditions. Towards this end we studied myelination in mice injected daily by GA, at postnatal Days 7–21. Immunohistological and ultrastructural analyses revealed significant elevation in the number of myelinated axons as well as in the thickness of the myelin encircling them and their resulting g‐ratios, in spinal cords of GA‐injected mice compared with their PBS‐injected littermates, at postnatal Day 14. Elevation in myelinated axons was detected also in the peripheral ventral roots of the motor nerves. GA induced also an increase in axonal diameter, implying an effect on the overall development of the nervous system. A prominent elevation in the amount of progenitor oligodendrocytes and their BrdU incorporation, as well as in mature oligodendrocytes indicated that the effect of GA is linked to increased proliferation and differentiation along the oligodendroglial maturation cascade. In addition, elevation in insulin‐like growth factor (IGF‐1) and brain‐derived neurotrophic factor (BDNF) was found in the white matter of the GA‐injected mice. Furthermore, a functional advantage in rotating rod test was exhibited by GA‐injected mice over their littermates at postnatal Day 21. These cumulative findings corroborate the beneficial effect of GA on oligodendrogenesis and myelination. GLIA 2014;62:649–665